Discovery of Synergistic Broadly Neutralizing Antibodies Targeting Non-Dominant Epitopes on SARS-CoV-2 RBD and NTD - Hualong Feng; Zuowei Wang; Ling Li; Yunjian Li; Maosheng Lu; Xixian Chen; Lin Hu; Yi Sun; Ruiping Du; Rongrong Qin; Xuanyi Chen; Liwei Jiang; et al. (Vaccines, 2025)
Background/Objectives: Identification and characterization of broadly neutralizing monoclonal antibodies from individuals exposed to SARS-CoV-2, either by infection or vaccination, can inform the development of next-generation vaccines and antibody therapeutics with pan-SARS-CoV-2 protection. Methods: Through single B cell sorting and RT-PCR, monoclonal antibodies (mAbs) were isolated from a donor who experienced a BA.5 or BF.7 breakthrough infection after three doses of inactivated vaccines. Their binding and neutralizing capacities were measured with ELISA and a pseudovirus-based neutralization assay, respectively. Their epitopes were mapped by competition ELISA and site-directed mutation. Results: Among a total of 67 spike-specific mAbs cloned from the donor, four mAbs (KXD643, KXD652, KXD681, and KXD686) can neutralize all tested SARS-CoV-2 variants from wild-type to KP.3. Moreover, KXD643, KXD652, and KXD681 belong to a clonotype encoded by IGHV5-51 and IGKV1-13 and recognize the cryptic and conserved RBD-8 epitope on the receptor-binding domain (RBD). In contrast, KXD686 is encoded by IGHV1-69 and IGKV3-20 and targets a conserved epitope (NTD Site iv) outside the antigenic supersite (NTD Site i) of the N-terminal domain (NTD). Notably, antibody cocktails containing these two groups of mAbs can neutralize SARS-CoV-2 more potently due to synergistic effects. In addition, bispecific antibodies derived from KXD643 and KXD686 demonstrate further improved neutralizing potency compared to antibody cocktails. Conclusions: These four mAbs can be developed as candidates of pan-SARS-CoV-2 antibody therapeutics through further antibody engineering. On the other hand, vaccines designed to simultaneously elicit neutralizing antibodies towards RBD-8 and NTD Site iv have the potential to provide pan-SARS-CoV-2 protection.